2012
DOI: 10.1149/1.3701544
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Oxygen Incorporation on the Defect Trap States of a-IGZO Thin-Film Transistors

Abstract: Thin-film transistors (TFTs) comprised of amorphous indiumgallium-zinc-oxide (a-IGZO) as the active channel layers were prepared by sputtering process at various Ar/O 2 gas flow ratios and their electrical properties were investigated. Device characterizations indicated that the TFT sample prepared at the condition of Ar/O 2 ratio = 20:0.6 exhibits the best performance with field-effect mobility (μ FE) = 5.2 cm 2 ⋅V −1 ⋅sec −1 , threshold voltage (V th) = 0.7 V, subthreshold gate swing (S.S.) = 0.9 V⋅decade −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Lo et al . demonstrated the effect of the gas (Ar:O 2 ) flow ratio on the trap density at the interface and reported a lower trap density for lower oxygen flow rates37. The TFT fabricated at OPP1 exhibited a hysteresis value of ~4 V at 30 V drain bias (SI, S5) along with the best device performance, including a mobility of 15.64 cm 2 /Vs, a threshold voltage of 6.5 V, and a I on/off of 4.5 × 10 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Lo et al . demonstrated the effect of the gas (Ar:O 2 ) flow ratio on the trap density at the interface and reported a lower trap density for lower oxygen flow rates37. The TFT fabricated at OPP1 exhibited a hysteresis value of ~4 V at 30 V drain bias (SI, S5) along with the best device performance, including a mobility of 15.64 cm 2 /Vs, a threshold voltage of 6.5 V, and a I on/off of 4.5 × 10 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Many research groups reported that interface defect density between gate insulator and IGZO, which has an amorphous structure. [12][13][14] One group suggested an experimental method for obtaining D it by metal-insulator-IGZO MIS capacitors. The other groups calculated the D it by SS value obtained TFT.…”
mentioning
confidence: 99%